How different advertising appeals (green vs. non-green) impact consumers' willingness to pay a premium for green agricultural products - Zheng, Manhua; Tang, Decong; Chen, Jianhong; Zheng, Qiujin; Xu, Anxin (Frontiers in Psychology, 2022)
Green food has exceptional impacts in addressing food safety and environmental challenges. However, consumers' perception of green food is not substantial, which results in a decline in consumption intention. Since advertising appeals can play a bridging role in resolving information asymmetry. This study is based on self-construal theory, chooses green agricultural products images and text as experimental stimuli, and analyzes the interaction and influence mechanism between advertising appeals and consumers' willingness to pay a premium for green agricultural products through three sets of experimental studies. The findings demonstrate that self-construal and green agricultural product advertising appeals interact to influence consumers' willingness to pay a premium for green agricultural products. Green perceived value is more strongly influenced by matching dependent self-construal and green advertising appeals than non-green advertising appeals. Green perceived value plays a full mediating role in this interactive effect. Green agricultural products companies should adopt different advertising strategies according to the various categories of consumers to enhance consumers' green perceived value and increase the willingness to pay a premium.